2019
DOI: 10.1002/pd.5620
|View full text |Cite
|
Sign up to set email alerts
|

Fetal fraction and noninvasive prenatal testing: What clinicians need to know

Abstract: The fetal fraction (FF) is a function of both biological factors and bioinformatics algorithms used to interpret DNA sequencing results. It is an essential quality control component of noninvasive prenatal testing (NIPT) results. Clinicians need to understand the biological influences on FF to be able to provide optimal post-test counseling and clinical management. There are many different technologies available for the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 91 publications
3
117
1
2
Order By: Relevance
“…Several factors, such as maternal weight, or body mass index (BMI), and gestational age (GA) can have an impact on the FF and, consequently, the test performance of the cell-free NIPT. 13,14 It has been demonstrated that the FF is inversely proportional to maternal BMI. One study showed that the average FF in women with a BMI of 35 to 39.9 kg/m 2 was 11.57%, significantly lower compared with a FF of 14.54% in women with a BMI <18.5 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several factors, such as maternal weight, or body mass index (BMI), and gestational age (GA) can have an impact on the FF and, consequently, the test performance of the cell-free NIPT. 13,14 It has been demonstrated that the FF is inversely proportional to maternal BMI. One study showed that the average FF in women with a BMI of 35 to 39.9 kg/m 2 was 11.57%, significantly lower compared with a FF of 14.54% in women with a BMI <18.5 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A primary driver of NIPS sensitivity for aneuploidy in a given maternal plasma sample is the fetal fraction (FF), which describes the proportion of cfDNA fragments that originate from the placenta. 6 For most samples, FF values are between 4% and 30%. 7 Many laboratories fail samples with FF<4% to diminish the risk of issuing false-negative reports.…”
Section: Introductionmentioning
confidence: 99%
“…Because the molecular and bioinformatic implementations of NIPS have evolved, diversified, and generally improved over time, sensitivity at progressively lower FF levels is platform-and laboratory-dependent. 6,8 Indeed, a recently published clinical-experience study demonstrated that a customized whole-genomesequencing (WGS)-based NIPS, which does not fail low-FF samples, can have comparable accuracy at high-FF and low-FF for the common aneuploidies on chromosomes 13, 18, and 21. 9 Though the common aneuploidies have long been the main focus of NIPS because of their frequency and highly penetrant phenotype, clinically actionable chromosomal anomalies span a range of sizes and can occur anywhere in the genome.…”
Section: Introductionmentioning
confidence: 99%
“…This showed that the risk for any maternal complication was higher (20.9%) for open fetal surgery compared to endoscopic surgery (6.2%). When considering only severe complications, the difference was smaller: 4.5% for open and 1.7% for endoscopic surgery. 36 However, in this review, around a quarter of studies reviewed were excluded as they failed to comment on maternal outcomes.…”
Section: Advances In Fetal Theraphymentioning
confidence: 90%
“…Being able to measure the relative proportion of placental and maternal DNA-the so-called fetal fraction (FF)-is now recognised as a crucial quality assurance metric. 3,4 However, laboratories currently use a variety of methods that are not directly comparable, with the Ychromosome-based method remaining the "gold standard" despite only being applicable to 50% of pregnancies. 5 Another challenge related to the problem of reproducibly measuring FF is the determining the tissue of origin of aberrant cfDNA when a source other than the placenta is suspected, for example, where a chaotic plasma genomic profile obtained during NIPT raises suspicion of a maternal neoplasm 6,7 If a suspected tumoural source of cfDNA could be inferred from the maternal plasma cfDNA, it would improve the management of these pregnant women.…”
Section: Fragmentomicsmentioning
confidence: 99%